"Blisko domu". Z historii określeń typu dom dziecka, dom wariatów, dom starców = "Near the house/the home". From the history of designations such as dom dziecka (orphanage), dom wariatów (madhouse), dom starców (old people`s home) - Pacuła, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the text describes the historical vocabulary that represents the concept of "home". He analyzes the secondary meanings of the lexeme "home", which is a component of expressions such as "dom starców" (old people?s home), "dom publiczny" (brothel), "dom dziecka" (orphanage), "dom kultury" (community centre).
Keywords: frazeologia; semantyka; historia języka; zmiany znaczeń; "dom" jako instytucja społeczna lub usługowa; phraseology; semantics; diachronic linguistics; change of meanings; "home" as a social or service institution